Measurement of Type 304L Stainless Steel and 16MND5 Ferritic Steel Density and Surface Tension: Possible Impact for Stratified Molten Pool. (2nd January 2019) - Chikhi, N.; Fouquart, P.; Delacroix, J.; Piluso, P.
Abstract: In-vessel retention (IVR) is an attractive strategy to mitigate a severe accident. However, because of low margins, it remains questionable for reactors of power of 1000 MW(electric) and higher. The success of the IVR strategy mainly depends on the mechanical behavior of the vessel after being ablated and on the inner thermal load, i.e., the heat flux transferred by the molten pool to the vessel, which has to remain lower than the critical heat flux. In some configurations, the stratification of the molten pool may lead to heat flux concentration in the thermal conductive metallic layer. An understanding of the metal layer behavior is fundamental in order to estimate the inner thermal load and requires knowing the liquid-metal physical properties, such as density and surface tension. In the present paper, original data of vessel thermophysical properties are proposed for the first time. Measurements of Type 304L stainless steel and 16MND5 ferritic steel density and surface tension have been made using the sessile drop method. Samples have been melted to form a drop on a yttria-stabilized zirconia substrate and heated up to 200°C above the melting point. Low Bond Axisymmetric Drop Shape Analysis has been used to estimate the sample density and surface tension and to propose correlations for the density and surface tension as a function of temperature. The influence of steel properties on metal layer cooling has been discussed. Especially, the sign of the metal temperature surface tension coefficient was found to be most likely positive. In this case, the Bénard-Marangoni flow is opposite to the Rayleigh-Bénard convection flow.